Evaluation of the genotoxicity of aqueous extracts of leaves and stems of Dolichandra unguis-cati (L.) L.G. Lohmann (Bignoniaceae) using the Allium cepa test - Florentín, Paul Alejandro (2019)
Fil: Florentín, Paul Alejandro. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales; Argentina.